Wave Breaker Model of Transmission Waves - Phetthanan Sukaphone; Buonkun Ounlesy Yaxasiht (Journal La Multiapp, 2021)
The wavelength, the wave height, and the depth of the water under which the waves travel are critical criteria for describing water waves. According to previous research, the depth and period of the waves have a significant effect on the propagation and reflection coefficients. The hollow breakwater's varied model is supposed to minimize wave reflection and propagation in addition to reducing wave reflection, due to its capacity to capture and reduce incident wave energy.